Increased colonic pain sensitivity in irritable bowel syndrome is the result of an increased tendency to report pain rather than increased neurosensory sensitivity. Issue 9 (4th May 2007) - Dorn, Spencer D; Palsson, Olafur S; Thiwan, Syed I M; Kanazawa, Motoyori; Clark, W Crawford; van Tilburg, Miranda A L; Drossman, Douglas A; Scarlett, Yolanda; Levy, Rona L; Ringel, Yehuda; Crowell, Michael D; Olden, Kevin W; et al.
Abstract : Objective: The aim was to determine whether lower visceral pain thresholds in irritable bowel syndrome (IBS) primarily reflect physiological or psychological factors. Methods: Firstly, 121 IBS patients and 28 controls underwent balloon distensions in the descending colon using the ascending methods of limits (AML) to assess pain and urge thresholds. Secondly, sensory decision theory analysis was used to separate physiological from psychological components of perception: neurosensory sensitivity (p(A)) was measured by the ability to discriminate between 30 mm Hg vs 34 mm Hg distensions; psychological influences were measured by the report criterion—that is, the overall tendency to report pain, indexed by the median intensity rating for all distensions, independent of intensity. Psychological symptoms were assessed using the Brief Symptom Inventory (BSI). Results: IBS patients had lower AML pain thresholds (median: 28 mm Hg vs 40 mm Hg; p<0.001), but similar neurosensory sensitivity (median p(A): 0.5 vs 0.5; p = 0.69; 42.6% vs 42.9% were able to discriminate between the stimuli better than chance) and a greater tendency to report pain (median report criterion: 4.0 ("mild" pain) vs 5.2 ("weak" pain); p = 0.003). AML pain thresholds were not correlated with neurosensory sensitivity (r = −0.13; p = 0.14), but were strongly correlated with report criterion (r = 0.67; p<0.0001). Report criterion was inversely correlated with BSI somatisation (r = −0.26; p = 0.001) and BSI global score (r = −0.18; p = 0.035). Similar results were seen for the non-painful sensation of urgency. Conclusion: Increased colonic sensitivity in IBS is strongly influenced by a psychological tendency to report pain and urge rather than increased neurosensory sensitivity.